Help-seeking for nonsuicidal self-injury in sexual minority adolescent and young adult females. Issue 2 (3rd April 2017) - Zaki, Landon F.; Gross, Madeline; Pachankis, John E.
ABSTRACT: Subgroups of sexual minority adolescent and young adult females (e.g., lesbian, bisexual, questioning) have been underrepresented in youth health research. However, evidence suggests they experience compromised coping strategies compared to heterosexual female peers and may be reluctant to seek professional help due to stigma. An Internet survey ( N = 482) examined nonsuicidal self-injury (NSSI), suicidal ideation, and help-seeking for NSSI in sexual minority and heterosexual adolescent and young adult females with histories of NSSI. Compared to heterosexual female youth, lesbian youth reported lower rates of NSSI and greater help-seeking from professionals, whereas bisexual youth reported greater suicidal ideation and a reluctance to seek professional help, favoring the help of romantic partners instead. Results extend research on help-seeking for risk behaviors in sexual minority female youth subgroups, while echoing the need to reduce sexual minority stigma in healthcare.